“What sort of a world is this, where killing and pain are the norm? What on earth is wrong with us?” Nature Strikes Back in Olga Tokarczuk’s "Drive Your Plow Overthe Bones of the Dead" (2009) - Sosnowska, Monika (2022)
The article seeks to explore the theme of nature’s revenge in Olga Tokarczuk’s novel Drive Your Plow Over the Bones of the Dead (2009, translated into English in 2018). The book may be classified as Anthropocene fiction or eco-fiction. Tokarczuk’s treatment of vengeful nature in Drive Your Plow… manifests as a literary representation of a physiology of an ecosystem in disequilibrium, pervaded by images of blood in a snowy landscape. The author renders her female protagonist, Janina Duszejko, a proponent and practitioner of a theory proposing that nature wreaks revenge on humans. Tokarczuk presents new ways of imagining agency beyond anthropocentrism. Drive Your Plow may serve as an example of literary fiction from which posthumanist reflections may spring, while simultaneously it oftentimes (even if unintentionally) draws on posthumanist philosophy and ethics. I also refer to Olga Tokarczuk biography and views in search of her environmental concerns and solutions.
Keywords: Tokarczuk, Olga